PROMOTING INTERNET IN RURAL AREAS THROUGH STUDENT TRAINING AT SAM N 1 BADIRI CENTRAL TAPANULI REGENCY - Rivon (PT. Lembaga Penerbit Penelitian Nusantara, 2025)
As the modern era progresses, Indonesia is one of the countries with a majority of its population actively using the internet. However, it's important to note that 10% of Indonesians don't yet understand how to use it. Many areas in Indonesia still experience delays in the adoption of technology, such as the Marangkayu sub-district in Kutai Kartanegara Regency, North Sumatra Province. Therefore, through community service activities, The author wishes to provide training on technology in the modern era, particularly in Badiri District, Central Tapanuli Regency. Because we believe that many people still don't understand digital technology, for example, how to operate a computer. Here, the author wants to share knowledge and information about digital technology, especially for students at SMAN N 1 Badiri, Tapanuli Regency. In this training, the author targets five meetings with material that will be presented, starting from computer operation, providing material on the use of Microsoft Word, Microsoft Excel, and Microsoft Office applications. Power Point. With training It is hoped that students will be able to understand how to operate computers, especially how to operate applications.